Testing electromagnetic field meters - Grudzinskі, Eugeniusz; Nichoga, Vitaliy; Prudyus, Ivan; Trzaska, Hubert (Publishing House of Lviv Polytechnic National University, 2012)
In this paper selected solutions of testing electromagnetic fields (EMF) meters used for the purposes of labour safety and environment protection are presented. У цій статті представлено деякі питання, пов’язані з тестуванням вимірювачів електромагнітного поля (ЕМП), які використовуються в галузях охорони праці та захисту навколишнього середовища.
Тестування вимірювачів електромагнітного поля
Keywords: exposure systems; the accuracy; uncertainty; embedded power supply